Gerakan Sosial Cinta Lingkungan dalam Menyelamatkan Pantai Cibery di Teluk Youtefa Kota Jayapura - Semuel D. Rorrong; Hiskia CM. Sapioper; Ramandei, Lazarus; Juliani Wairata (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Cybery Beach is a beach that has enormous potential to be developed, besides being very close to the center of Jayapura, this beach is the only beach located right next to the Youtefa Bridge and the Youtefa Bay Estuary so it has enormous potential to be developed because it is visited by many visitors in Jayapura city, Cybery Beach is also located on the ringroad and eastward with Holtekamp Beach, environmental safety is a shared responsibility of both the government, the community, visitors in keeping the environment clean and well maintained.The purpose of this service activity is to socialize the Love Environment Movement carried out by the Cenderawasih University Service Team. Public awareness, especially visitors to Cybery beach, of the importance of maintaining environmental cleanliness is still very lacking because there are still people who litter, especially plastic waste used as food wrappers which are left scattered around the beach. The importance of understanding the concept of environmental safety for the community from an early age so that environmental cleanliness can be enjoyed by all communities and public benefits can be achieved through environmental hygiene social action. The basic nature of environmental management and conservation is the main capital for the development of natural resources and human resources so that an active role of the community is needed to strive for environmental conservation.The results achieved in the service are that with this activity, it can foster enthusiasm in saving the environment, even through this activity the Love the Environment Movement can be campaigned, especially in saving Cybery Beach.